2012
DOI: 10.1002/asi.22754
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the benefits of international scientific collaboration

Abstract: We analyze the benefits in terms of scientific impact deriving from international collaboration, examining both those for a country when it collaborates and also those for the other countries when they are collaborating with the former. The data show the more countries there are involved in the collaboration, the greater the gain in impact. Contrary to what we expected, the scientific impact of a country does not significantly influence the benefit it derives from collaboration, but does seem to positively inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
48
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(66 citation statements)
references
References 23 publications
1
48
0
4
Order By: Relevance
“…This feature is probably related to the way products relate to the contexts in which they are produced. In the field of psychology, recent studies show that high productivity is concentrated in some countries; therefore the way these researchers collaborate could be used as a model for other countries to increase research (García-Martínez et al, 2012;Guerrero Bote et al, 2013). Geographical proximity and language could be seen as factors that could enhance communication.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This feature is probably related to the way products relate to the contexts in which they are produced. In the field of psychology, recent studies show that high productivity is concentrated in some countries; therefore the way these researchers collaborate could be used as a model for other countries to increase research (García-Martínez et al, 2012;Guerrero Bote et al, 2013). Geographical proximity and language could be seen as factors that could enhance communication.…”
mentioning
confidence: 99%
“…In general, international cooperation is associated with higher visibility and higher impact. Various studies have tried to characterize the collaboration parameters by regions (Guerrero Bote et al, 2013). Thus, one collaboration analysis between China and other countries demonstrated that while the growth of the number of publications increases among the countries of high economic level, the impact of these publications does not increase in the same way (He, 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These collaborations help promote and proliferate research [13,14], therefore, they should be encouraged, supported and monitored. Studies [13,15,16,17] indicate that there is a direct relationship between scientific collaboration and creation of new knowledge. Coauthorship is one of these collaborations.…”
Section: Sna Metrics For Academic Social Networkmentioning
confidence: 99%